A Socioreligious Analysis of Islamic New Year Commemorative Practices in Kubang Utara Sikabu Village, Lembah Segar, Sawahlunto - Dewi, Sandra; Mevya, Eva Azharina; Oktaviandini, Dila; Putri, Nayla Dwi; Rahmatika, Zulfa (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The Islamic New Year, especially on the 1st of Muharram, is not merely a religious ceremony but also holds significant educational value, particularly in shaping character and strengthening Islamic values. This study aims to describe the form, content, and impact of the 1st Muharram religious study activities held at the Al-Kautsar Mosque, Mata Air Hamlet, Kubang Utara Sikabu Village, Lembah Segar District, Sawahlunto City. The method used is descriptive qualitative with a content analysis approach. The results show that these religious studies contain the values of hablumminallah (human relationship with God) and hablumminannas (relationship with others), and are an effective means of non-formal education in the community. In addition, these activities also strengthen social solidarity, increase community participation, and preserve local values in accordance with Islamic teachings. This 1st Muharram religious study can be used as a concrete example of Islamic education practices that are alive in the community and are able to shape religious, caring, and moral characters.